P‐Type Dye‐Sensitized Solar Cells with a CdSeS Quantum‐Dot‐Sensitized NiO Photocathode for Outstanding Short‐Circuit Current. (21st October 2015) - Kong, Wenping; Li, Shengjun; Chen, Zeng; Wei, Chaochao; Li, Wei; Li, Tao; Yan, Ying; Jia, Xiyang; Xu, Binghua; Zhang, Weifeng
Abstract : CdSeS quantum dots (QDs) are firstly introduced into a NiO photocathode for photocathodic dye‐sensitized solar cells (p‐DSCs). The optimized sample exhibits a short‐circuit density (14.68 mA cm −2 ) and power conversion efficiency (1.02%) that are almost one order of magnitude higher than the reported value of p‐QDSCs. Steady‐state photoluminescence and time‐resolved photoluminescence measurements indicate that the photoexcited holes can be almost completely injected from CdSeS QDs into the valence band of NiO. At the same time, it can be observed from electrochemical impedance spectra measurements. Abstract : CdSeS quantum dots (QDs) are introduced for the first time into a NiO photocathode to fabricate photocathodic dye‐sensitized solar cells (p‐DSCs). In these p‐DSCs, photoexcited holes are efficiently injected from the CdSeS QDs into the NiO and collected by the conduction substrates. The optimized sample shows the highest J sc (14.68 mA cm −2 ) and power conversion efficiency (1.02%) values recorded for QD‐sensitized p‐DSCs.